2022
DOI: 10.3389/fpubh.2022.929764
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Community Case Management Utilization Status and Associated Factors Among Caretakers of Sick Children Under the Age of 5 Years in West Shewa, Ethiopia

Abstract: ObjectiveTo assess the utilization status and associated factors of integrated community case management (ICCM) of caretakers with <5 years of sick children.MethodsCommunity-based cross-sectional study was employed with caretakers whose child was sick in the last 3 months before data collection. Bivariate and multivariable logistic regression analyses were employed.ResultsAbout 624 respondents participated in the study; 325 (52.1%) utilized integrated community case management. Caring for children betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
1
Order By: Relevance
“…However, the study finding is different from those of a study conducted in Kabarole by (Rukundo, Kwesiga, & Ario, 2016) on the implementation of ICCM policy which reported the higher percentage of 52.3% of care givers had utilized ICCM services. This finding is also not similar to those of a study by (Debel & Nigusso, 2022) in West Shewa, Ethiopia that reported utilization of the integrated community case management by caretakers for children under 5 years old to be at 57% which is way higher than the uptake level reported in Apac district. These differences in the findings could be attributed to the differences in the settings where the study was conducted.…”
Section: Level Of Uptake Of Iccm Services Among Caregivers Of Childre...contrasting
confidence: 99%
“…However, the study finding is different from those of a study conducted in Kabarole by (Rukundo, Kwesiga, & Ario, 2016) on the implementation of ICCM policy which reported the higher percentage of 52.3% of care givers had utilized ICCM services. This finding is also not similar to those of a study by (Debel & Nigusso, 2022) in West Shewa, Ethiopia that reported utilization of the integrated community case management by caretakers for children under 5 years old to be at 57% which is way higher than the uptake level reported in Apac district. These differences in the findings could be attributed to the differences in the settings where the study was conducted.…”
Section: Level Of Uptake Of Iccm Services Among Caregivers Of Childre...contrasting
confidence: 99%